Agreement analysis of oscillometric devices in the measure of resting heart rate in breast cancer survivors - Palma, Mariana R. [UNESP]; Vanderlei, Luiz C.M. [UNESP]; Ribeiro, Fernanda E. [UNESP]; De Andrade, Rafaela C.C. [UNESP]; Fregonesi, Cristina E.P.T. [UNESP]; Freitas Júnior, Ismael F. [UNESP]; Christofaro, Diego G.D. [UNESP] (Wolters Kluwer, 2018)
ObjectiveThe aim of this study was to verify the reproducibility of an oscillometric device in the measurement of resting heart rate (RHR) in breast cancer survivors.MethodsThis study included 85 breast cancer survivors with a mean age of 58.87±10.03 years. For the RHR evaluation, the equipment used was the Omron HEM 742, electronic and digital arm device, for measurement of blood pressure and heart rate (HR), with automatic cuff inflation and deflation. At the same time as the oscillometric measurement, HR was measured by the HR monitor Polar RS800 CX, which has been validated previously for HR uptake. The HR value obtained by the cardiofrequency meter was registered at the same time that the Omron device measured blood pressure and HR values.ResultsIt was observed that the RHR values were very close in both devices and that the correlation values and intraclass correlation coefficient were high. These results were replicated when the female breast cancer survivors were stratified by age group. The agreement values presented by the Bland-Altman analysis showed good values; both for the entire sample and stratified by age, few cases were outside beyond 95% confidence interval range.ConclusionThe present study showed that the oscillometric device used presented good values of reproducibility in the detection of RHR values in breast cancer survivors compared with a cardiac monitor.
Keywords: arterial pressure; breast neoplasms; cardiovascular; diagnostic techniques; heart rate